The Concept Of Kafa'ah In Marriage According To The Views Of Ulama Of Amuntai Tengah District - Al Rosyid, Ahmad Saifuddin; Hidayah, Ahdiyatul (Muhammadiyah University of Surabaya, 2023)
Marriage is a bond of sacred and sacred rope that has been recommended to be carried out by people who have Muslim status. In marriage, there is a need for harmony between prospective husband and wife or commonly called kafa'ah, both in terms of belief and offspring. The balance of couples in the household is able to foster true happiness between the two, and it also determines whether or not a person will be able to build a household ark. Kafaah in the marriage bond is very important as a way to achieve the goal of a happy marriage based on sakinah, mawaddah and warahmah. So that with the achievement of this goal, a harmonious family can be easily formed. Therefore, before marriage, prospective wives and husbands are encouraged to know each other, so as to understand each other's life status both from their personal, religious, social status and the condition of their daily lives.